Non-price aspects of an export promotion strategy for the Caribbean. - McIntyre, Arnold (1990)
Outlines some key patterns and sequence of export marketing derived from a detailed analysis of the East Asian economies which have been the most successful developing countries in the area. Looks at the most effective, least cost forms of institutional support to export marketing for small manufacturing firms in the Caribbean.